Achondroplasia and hypochondroplasia. Comments on frequency, mutation rate, and radiological features in skull and spine. Issue 2 (April 1979) - Oberklaid, F; Danks, D M; Jensen, F; Stace, L; Rosshandler, S
Abstract : An attempt was made to ascertain all the dwarfs in the State of Victoria. The incidence of achondroplasia proved to be approximately 1 in 26, 000 live births in the period 1969 to 1975 when ascertainment was nearly complete. This indicates a mutation rate of 1.93 X 10(-5) per generation in this locus. Paternal age was shown to influence mutation. Ascertainment in earlier years of the study was low despite the very great effort made to find all cases. Patients with hypochondroplasia were particularly difficult to find. However, 25 cases were found for study. Overlap between hypochondroplasia and achondroplasia was found in all features except the facial appearance (which was the basis of definition). Achondroplasia was more severe in all regards, but some individuals with hypochondroplasia were very short and some had extreme degrees of spinal canal stenosis. The classical measurements used to describe the skull changes in acondroplasia failed to distinguish this condition from hypochondroplasia. More efficient indices were devised, but visual assessment of the size of the facial region compared to that of the cranial valult proved more reliable than any index. The clinical distinction based upon facial appearance remains the arbitrary basis of definition.